Parenting beyond your capacity : connect your family to a wider community - Joiner, Reggie; Nieuwhof, Carey (Colorado Springs, Colo. : David C. Cook, 2010)
When parents work in tandem with the faith community to raise their children, they increase their parenting capacity exponentially. Most parents have so many demands on their time that they can't be the kind of parent they desire to be. They need to know the Orange Factor: Two combined influences will make a greater impact on kids than just two influences. And it's true. Parents who partner with the faith community are the best way to bring the next generation into the family of God-and keep them there.
Keywords: Christian education of children; Church work with families; Christian education of children; Church work with families